A Systematic Review and Meta-analysis of Endovascular Popliteal Aneurysm Repair Using the Hemobahn/Viabahn Stent-Graft. (June 2015) - Patel, Shaneel R.; Hughes, Cían O.; Jones, Keith G.; Holt, Peter J. E.; Thompson, Matt M.; Hinchliffe, Robert J.; Karthikesalingam, Alan
Purpose: To perform an evidence synthesis study to assess outcomes of endovascular repair of popliteal artery aneurysms (PAAs) using the Hemobahn or Viabahn stent-graft.Methods: A systematic literature review was conducted conforming to established standards to identify articles published between 1996 (the date of introduction of the Hemobahn stent-graft) and 2013 reporting stent-graft repair of PAAs in at least 10 patients. The data were pooled for Kaplan-Meier analysis of primary and secondary patency rates [presented with 95% confidence intervals (CIs)] as the primary outcomes. Random effects meta-analysis was performed for secondary outcomes that included rates of reintervention, endoleak, stent-graft fracture, and limb salvage.Results: Fourteen studies reported outcomes for 514 PAAs. There was considerable heterogeneity in reporting standards among studies. Pooled primary and secondary patency rates were 69.4% (95% CI 63.3% to 76.2%) and 77.4% (95% CI 70.1% to 85.3%), respectively, at 5 years. Five studies (including only one randomized controlled trial) compared surgical to endovascular repair; no difference was found in primary patency on evidence synthesis (hazard ratio 1.30, 95% CI 0.79 to 12.14, p=0.189).Conclusion: Stent-graft repair provides a feasible treatment option for anatomically suitable PAAs. Further studies are required to optimize both patient selection and follow-up protocols.